Carbon dioxide concentration and its stable carbon isotope composition in Allan Hills ice cores - Bender, Michael; Brook, Edward J.; Higgins, John; Yan, Yuzhen (IEDA: US Antarctic Program Data Center, 2019)
This file includes the concentration of carbon dioxide (CO2) and methane (CH4) and the stable carbon isotope composition of CO2 in Allan Hills ice cores (ALHIC1502 and ALHIC1503).